1960
DOI: 10.4039/ent92881-12
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Assessment of Parasitization by Apanteles fumiferanae Vier. and Glypta fumiferanae (Vier.) on Spruce Budworm Larvae

Abstract: Sampling to obtain valid estimates of the degree of parasitism in natural populations of insects presents a difficult problem to the quantitative-minded investigator. The method used must adhere to the principles of random sampling, yet it must be truly representative with respect to the occurrence of the parasite in its sampling universe, the host insect, in both time and space.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

1977
1977
1996
1996

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…Parasitoids that cause their hosts to select different microhabitats could reduce predation or hyperparasitism (cf. McGugan, 1955;Lewis, 1960;Van Sickle and Weseloh, 1974). Lewis (1960) suggested that microhabitat differences were responsible for lower mortality of parasitized spruce budworm larvae (Choristoneura fumijerana [Clem.…”
Section: Discussionmentioning
confidence: 99%
“…Parasitoids that cause their hosts to select different microhabitats could reduce predation or hyperparasitism (cf. McGugan, 1955;Lewis, 1960;Van Sickle and Weseloh, 1974). Lewis (1960) suggested that microhabitat differences were responsible for lower mortality of parasitized spruce budworm larvae (Choristoneura fumijerana [Clem.…”
Section: Discussionmentioning
confidence: 99%
“…Host behaviour modification by insect parasitoids has generally been inferred, on the basis of differences in habitat distribution of parasitized and nonparasitized hosts (Lewis, 1960;Ehrlich, 1965;Tostowaryk, 1971;Shapiro, 1976), or within canopy distribution of caterpillars containing early and late instar parasitoid larvae (Stamp, 1981). However, these distributions could reflect patterns of parasitoid foraging behaviour rather than modified host behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…fumiferanae readily attacks free-moving larvae but has difficulty in penetrating hosts in hibernacula with its short ovipositor, whereas Miller (1959) suggested that the opposite may be true. Lewis (1960) and Miller (1959) agreed that G . fumiferanae searched primarily for larvae in hibernacula.…”
Section: Hosts Attacked By Both Apanteles and Glyptamentioning
confidence: 90%